2019
DOI: 10.1016/j.jcot.2018.05.012
|View full text |Cite|
|
Sign up to set email alerts
|

Does vitamin D deficiency influence the incidence and progression of knee osteoarthritis? – A literature review

Abstract: Objectives: Vitamin D has been believed to have a bearing in the pathogenesis of knee osteoarthritis (OA). This study was done to search the literature and review the correlation between vitamin D levels in knee OA in the adult population and the outcome of vitamin D supplementation in knee OA. Methods: An exhaustive search of Pub Med and Cochrane library database was done with keywords vitamin D, knee and osteoarthritis for a period from Jan 2005 to December 2015. All Randomized Control Trials (RCT), Cohort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
(55 reference statements)
0
26
0
1
Order By: Relevance
“…Many observational and longitudinal studies across the world reported a higher prevalence of KOA and increased risk of disease progression in vitamin D deficient patients[ 5 - 13 ]. However, few studies contradicted this association[ 14 - 20 ]. A recent review by Vaishya et al[ 20 ] reported that there was moderate evidence of a positive association between VDD and progression of radiographic OA (ROA).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many observational and longitudinal studies across the world reported a higher prevalence of KOA and increased risk of disease progression in vitamin D deficient patients[ 5 - 13 ]. However, few studies contradicted this association[ 14 - 20 ]. A recent review by Vaishya et al[ 20 ] reported that there was moderate evidence of a positive association between VDD and progression of radiographic OA (ROA).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies contradicted this association[ 14 - 20 ]. A recent review by Vaishya et al[ 20 ] reported that there was moderate evidence of a positive association between VDD and progression of radiographic OA (ROA). They reported limited evidence for a positive correlation between VDD and cartilage volume loss.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between vitamin D and knee OA has been investigated in a recent systematic review of 11 studies, which concluded that although vitamin D deficiency is associated with knee OA, the evidence regarding this association is inconsistent [53]. The studies included in the review were largely of cohort and cross-sectional design but also included two RCTs.…”
Section: Vitamin Dmentioning
confidence: 99%